Revisiting Agamben’s Homo Sacer: Sovereign Power and Bare Life – A Critical Review - Md. Lab Hossain; Mahmuda Akter (Law and Society Students' Journal)
Agamben is one of the most influential living thinkers in the world, and within the constellation of his oeuvre, the highly influential Homo Sacer: Sovereign Power and Bare Life (1998), explores the relationship between sovereignty, law, and the human condition, focusing on how modern political power is related to human life and how this power can inclusively exclude people from the protection of the law. In this book, Agamben examines the paradox of sovereignty, its relation to the state of exception, and the production of bare life within this framework, which he terms homo sacer . Furthermore, his book insight into sovereignty, biopolitics, and exclusion are crucial for understanding contemporary issues likes state of exception, state surveillance, migration crises, human rights violations, and democratic erosion, especially in an era of rising political instability and authoritarianism, urging a rethinking of power structures and inclusion. Therefore, this book will serve as a trajectory not only for understanding the Western political sphere but also for the liberal democratic context of the subcontinent.